The Issue of Economic and Entrepreneurial Activity Correlation in the Light of Constitutional Changes - Serobyan , D. (Bulletin of Yerevan University C: Jurisprudence, 2018)
The modern legal regulation of economic relations in the Republic of Armenia has undergone significant changes in comparison with the legal regulation of the same economic relations prior to Armenia’s independence. These changes are fundamental and primarily pursue the goal of developing the very economic relations and in particular business relations, protection and promotion of free economic competition for the development of entrepreneurship and consumer protection. In this article, based on the analysis of theoretical provisions, current legislation and judicial practice, an attempt is made to identify the correlation of economic and business activities, comparison of signs of economic and entrepreneurial activity. In the light of the constitutional and legal reforms recently carried out in the Republic of Armenia, the author concludes that doctrinal and legislative establishment of entrepreneurial activity as a type of economic activity is reasonable.